2016
DOI: 10.1371/journal.pone.0150104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Divergent Lineage Porcine Pestivirus in Nursing Piglets with Congenital Tremors and Reproduction of Disease following Experimental Inoculation

Abstract: Congenital tremors is a sporadic disease of neonatal pigs characterized by action-related repetitive myoclonus. A majority of outbreaks of congenital tremors have been attributed to an unidentified virus. The objectives of this project were to 1) detect potential pathogen(s) in samples from piglets with congenital tremors and 2) develop an infection model to reproduce disease. Using next-generation sequencing, a divergent lineage pestivirus was detected in piglets with congenital tremors. The virus was origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
229
3
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(262 citation statements)
references
References 13 publications
16
229
3
14
Order By: Relevance
“…The two affected litters showed some piglets with moderate to severe clinical signs of disease, a majority of piglets with mild clinical signs and even some with no clinical signs, similar to what we observe at farms with outbreaks. Our findings are in agreement with the findings by Arruda et al, who experimentally infected fetuses [15], whereas we infected pregnant gilts. Arruda et al [15] also observed large variation in the severity of clinical signs within affected litters.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The two affected litters showed some piglets with moderate to severe clinical signs of disease, a majority of piglets with mild clinical signs and even some with no clinical signs, similar to what we observe at farms with outbreaks. Our findings are in agreement with the findings by Arruda et al, who experimentally infected fetuses [15], whereas we infected pregnant gilts. Arruda et al [15] also observed large variation in the severity of clinical signs within affected litters.…”
Section: Discussionsupporting
confidence: 94%
“…All 99 samples (100%) from piglets with disease sampled at 10 different farms were PCR-positive, whereas only six of 66 (9%) of the controls without clinical signs were positive. This strong association was also found by Arruda et al [15]: 15/16 serum samples of congenital tremor piglets PCR-positive, four controls negative; and Postel et al [24]: 6/6 congenital tremor serum sample positive, 2/2 controls PCR-negative.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations